Effect of Work Motivation, Work Discipline, and Compensation on Employee Performance at PT Super Unggas Jaya Unit Rpa Kuningan, Poultry Processing Company - Santosa, Wildan Adhi; Herlambang, Mohamad Rhenaldi; Maryam, Siti (International Journal of Business, Economics, and Social Development, 2025)
Analyzing affects of compensation, work motivation, and work discipline on employee performance at PT Super Unggas Jaya Kuningan RPA Unit is the goal of this study. 151 respondents were selected through purposive sampling, and data were gathered using a quantitative approach and an associative method. Applying Partial Least Squares Structural Equation Modeling (PLS-SEM) method and SmartPLS 3.0 software, data analysis was carried out. While compensation had no discernible impact on employee performance, results demonstrated work motivation and discipline had a positive and significant impact. According to R2 value of 0.571, 57.1% of variation in employee performance is able to be clarified by three variables taken together.The f² test revealed that work motivation exerts a strong influence (f² = 0.516), work discipline exerts a moderate influence (f² = 0.196), and compensation exerts a very small influence (f² = 0.033). This study recommends that companies prioritize strengthening work motivation and work discipline in human resource management strategies. Meanwhile, the role of compensation needs to be studied further to understand its influence more deeply on employee performance.